1993
DOI: 10.1042/bj2910907
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of penicillin acylase from Kluyvera citrophila by N-ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline: a case of time-dependent non-covalent enzyme inhibition

Abstract: Penicillin acylase (PA) from Kluyvera citrophila was inhibited by N-ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline (EEDQ), a specific carboxy-group-reactive reagent. Enzyme activity progressively decreased to a residual value depending on EEDQ concentration. Neither enzymic nor non-enzymic decomposition of EEDQ is concomitant with PA inactivation. Moreover, enzyme re-activation is achieved by chromatographic removal of EEDQ, pH increase or displacement of the reagent with penicillin G. It was then concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Only those sites not already bound with a ligand are apparently vulnerable to EEDQ-induced inactivation. This apparent competition is consistent with a two-step mechanism of action for EEDQ, with the first step being a rapid and competitive binding to a recognition site, and the second step being a very slow reaction, and hence virtually irreversible, as has been described for the inactivation of an enzyme by EEDQ (Martin, Mancheño, & Arche, 1993). Protection from EEDQ-induced reduction in the density of dopamine receptors therefore provides an indication of in vivo occupation of both D 1 -like and D 2 -like receptor subtypes by endogenous and/or exogenous ligands (Burger & Martin-Iverson, 1993, 1994; Martin-Iverson & Burger, 1995).…”
supporting
confidence: 84%
“…Only those sites not already bound with a ligand are apparently vulnerable to EEDQ-induced inactivation. This apparent competition is consistent with a two-step mechanism of action for EEDQ, with the first step being a rapid and competitive binding to a recognition site, and the second step being a very slow reaction, and hence virtually irreversible, as has been described for the inactivation of an enzyme by EEDQ (Martin, Mancheño, & Arche, 1993). Protection from EEDQ-induced reduction in the density of dopamine receptors therefore provides an indication of in vivo occupation of both D 1 -like and D 2 -like receptor subtypes by endogenous and/or exogenous ligands (Burger & Martin-Iverson, 1993, 1994; Martin-Iverson & Burger, 1995).…”
supporting
confidence: 84%
“…The 2 × 2 cm coupons were UV-ozone-irradiated from one side with a Jelight Co. model 42 UVO Cleaner (Irvine, CA, USA) for 15 min to create carboxylic acid groups on their surfaces , (this step will be referred as UV-O 3 ). To create surface anhydride groups (and make the PP surface reactive toward the primary amines of PEI through nucleophilic attack), UV-O 3 coupons were shaken for 2 h at room temperature in a 0.1 mM solution of EEDQ in 50 mM MES buffer (pH 5.5) . Before mixing with the MES buffer, the necessary amount of EEDQ was dissolved in a volume of methanol equal to <1% of the final volume of the mix.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…To create surface anhydride groups (and make the PP surface reactive toward the primary amines of PEI through nucleophilic attack), UV-O 3 coupons were shaken for 2 h at room temperature in a 0.1 mM solution of EEDQ in 50 mM MES buffer (pH 5.5). 30 Before mixing with the MES buffer, the necessary amount of EEDQ was dissolved in a volume of methanol equal to <1% of the final volume of the mix. This step will be referred to as EEDQ.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…[1,17] However, in spite of the advantages of this approach, the immobilization should not negatively interfere with the interaction of the substrates with the active centre and the conformational changes the enzyme undergoes therein. [18][19][20] Consequently, the influence of any structural change (i.e., a distortion of the amino acid residues involved in catalysis and/or in substrate binding) induced by immobilization cannot be underestimated. In fact, it has been reported that immobilization influences the catalytic properties of PGA, [21] depending on the type of matrix, the binding chemistry and the microenvironment created around the active site.…”
Section: Introductionmentioning
confidence: 99%